FAO/IPGRI technical guidelines for the safe movement of cacao germplasm - Frison, Emile A.; Diekmann, M.; Nowell, D.; Food and Agriculture Organization of the United Nations; International Plant Genetic Resources Institute (2000)
Replaces:Frison, E.A. and Feliu,E. (eds). 1989. FAO/IBPGR Technical Guidelines for te Safe Movement of Cocoa Germplasm. Food and Agriculture Organization of the United Nations, Rome/International Board for Plant Genetic Resources, Rome. Available only electronically as a Portable Document Format (PDF)